Fuzzy Translation and Fuzzy Multiplication on D-Algebras - Mohammed Khalid Shahoodh; Montaser I. Adwan (Tikrit Journal of Pure Science)
The concept of fuzzy set (FS) is one of the beautiful branches in Mathematics. This concept was initiated by Zadeh [1]. Since that time, many studies have been considered this concept by different ways in the field of pure and applied Mathematics. In this article, we introduced the notion of FT and FM on a D-algebras where FT is a fuzzy Translation and FM is a fuzzy Multiplication. We proved some characterizations of FT and FM of sub-algebra and d-ideal of a D-algebras  Moreover, the notion of FM-αλ-T has been investigated on the D-algebras  Furthermore, some results on the d-homomorphism of FT and FM which based on the fuzzy d-ideal of a D-algebras are presented.